Execution time of mawashi-gueri in karate competition and training situations - Fernando, C.; Vicente, A.; Lopes, H. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Training is a preparation for the competition; however, in order to actually accomplish this aim efficiently it is necessary that the conditions under which it is made suit the training goals (Almada et al., 2008). Understanding the inherent variables in the ecological situation of a mawashi-gueri is essential to build coherent training models but it is also important to test whether the starting conjectures are consistent with the data obtained. Methods: In a sample of 5 senior level male individuals with experience in karate (karateka) we recorded and measure the execution time of mawashi-gueri in three different situations: 1) In a combat situation in competition; 2) In a training situation where from the usual displacement movement in combat the karateka performed the mawashi-gueri for a pre-defined area; 3) In a training situation starting from a static position the karateka performed the mawashi-gueri. The films from each situation were edited with Adobe Premiere Pro C4, with a breakdown of 25 frames/minute and quantified the time of 7 mawashi-gueri for every situation and every karateka. Results: The average time for the execution of mawashi-gueri in situation 1) was 377ms, in situation 2) 398ms and in situation 3) 598ms. The standard deviation was respectively 0.45ms, 0.27ms and 0.44ms. In all the situations the values range was 400ms, being the maximum value of 680ms and the minimum of 280ms. Discussion: The obtained data from the ecological situation of combat (228-248ms) are far below those known for the execution time of the mawashi-gueri, including the data presented by Villani et al. (2009) where the times where reported between 610-640ms. Also Mori et al. (2002) in punching and kicking techniques indicate values between 430-660ms. This difference is easily explained by the fact that the values presented by these studies were collected in laboratorial situations where the karateka starts moving from a static position. However, through the experimental situations made, we have verified that even in an isolated situation of mawashi-gueri training it is possible that the karatekas present time values closest to the ecological situation if the exercise is designed with this concern. Moreover, we believe that the difference in the execution times of mawashi-gueri in a static situation (situation 3) found when compared to data from other studies may have been caused by the fact that karatekas were influenced by the other held situation (situation 2) or even by their competition experiences.